A Vindication of Politics : On the Common Good and Human Flourishing - Wright, Matthew D. (Book collections on Project MUSE., 2019)
"Natural law political theory grounds the authority of law in the law's capacity to advance the common good, but questions about what this common good is and how it relates to political life remain highly contested. The influential new natural law theory of John Finnis reduces political association to the operation of government and makes it a merely instrumental good that serves to secure and facilitate individual and social goods. Political community, on this account, does not realize any further human good not already experienced in smaller human communities. In A Vindication of Politics, Matthew Wright challenges this account and argues that political community itself realizes an aspect of social life intrinsic to full human flourishing. Wright develops an account of the political common good that is both inclusivist and distinctive--that is to say, it includes within its orbit the diverse goods of individuals and other associations, and it recognizes the good of the political association itself. Drawing on the work of Edmund Burke and the example of Abraham Lincoln, Wright argues that political community has its own distinctive goods, including civic friendship and political culture, embodied in its history, institutions, practices, and ideals. Individuals do not have to run for office to be engaged in the political common good. Participation in the vibrant cultural life of one's political community is an intrinsic part of the common good"--